Benzodiazepine receptor quantification in Huntington's disease with [123I]iomazenil and SPECT - Pinborg, L H; Videbæk, C; Hasselbalch, S G; Sørensen, S A; Wagner, A; Paulson, O B; Knudsen, G M (Journal of neurology, neurosurgery and psychiatry, 2001)
OBJECTIVES Increasing evidence suggests that metabolic changes predate neuronal death in Huntington's disease and emission tomography methods (PET and SPECT) have shown changes in glucose consumption and receptor function in early and possibly even presymptomatic disease. Because the GABAA-benzodiazepine receptor complex (BZR) is expressed on virtually all cerebral neurons BZR density images may be used to detect neuronal death. In this study the regional cerebral [123I]iomazenil binding to BZR was determined in patients with Huntington's disease and normal controls by a steady state method and SPECT. METHODS Seven patients mildly to moderately affected by Huntington's disease and seven age matched controls were studied. Brain CT was performed on all subjects. In each subject two [123I]iomazenil-SPECT measurements were acquired—one with and one without infusion of flumazenil. The affinity constant of flumazenil (Kd) was calculated from the paired distribution volumes (DV) and the free plasma flumazenil concentration. The distribution volume of [123I]iomazenil in the unblocked condition (DV0) reflects the ratio between BZR density and Kd. RESULTS Flumazenil Kd was similar in the Huntington's disease group and the control group (11.3 v 11.2 mM). For the Huntington's disease group a 31% reduction in striatal DV0 (p=0.03) was found. In the cortical regions, DV0 was similar in patients and in controls. In Huntington's disease, DV0 correlated significantly with functional capacity (p=0.04) and chorea symptoms (p=0.02). The clinically least affected patients displayed DV0s within the range of those of the control group (19–35 ml/ml). CONCLUSIONS The finding of an unchanged Kd of flumazenil in patients indicates that the BZR is functionally intact in Huntington's disease. That is, the reduction in DV0 for BZR represents a selective decrease in the number of striatal BZRs. DV0 significantly correlated with functional loss and [123I]iomazenil-SPECT could be an important tool for validation of the effect of future therapeutic strategies aimed at limiting oxidative stress and free radicals in Huntington's disease.